(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The study of all the aspects is made possible by knowing prior to investigation the points that need to be addressed. Dr. Boenninghausen added the crucial knowledge in the form of hexa-mater and answered the crucial question of characteristic value of symptoms as the therapeutic selection of remedy3. It is crucial to understand the value of symptoms before the selection of the similimum.